ELASTICSEARCH AI ARCHITECTURE FOR EDUCATIONAL FINANCIAL SYSTEMS: A TECHNICAL DEEP DIVE - Gaurav Krishan Ohri, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article presents a comprehensive technical analysis of implementing Elasticsearch AI architecture in educational financial systems, focusing on integrating advanced data processing, search capabilities, and security measures. The article explores the development of a sophisticated system architecture that harmonizes distributed processing with real-time operations, incorporating natural language processing for enhanced user interactions. The article examines the implementation of robust security protocols, administrative tools, and system integration methods while maintaining high performance and reliability. The system achieves significant improvements in transaction processing, query resolution, and overall system efficiency by adopting modern caching strategies and load-balancing techniques. The article demonstrates how business intelligence capabilities and advanced analytics transform complex financial data into actionable insights, enabling educational institutions to optimize payment processing operations. This article contributes to the field by presenting a scalable, secure, and efficient solution for managing educational financial transactions while ensuring seamless integration with existing systems and maintaining compliance with financial regulations.